1993
DOI: 10.1016/s0886-3350(13)80349-5
|View full text |Cite
|
Sign up to set email alerts
|

Implanting two posterior chamber intraocular lenses in a case of microphthalmos

Abstract: A 31-year-old male with bilateral microphthalmos and a history of severe refractive amblyopia presented with early nuclear sclerosis. Intraocular lens calculations determined the patient would need about a 46.0 diopter power intraocular lens in both eyes to achieve satisfactory vision postoperatively. When no manufacturer could or was willing to make such a high-power lens, we chose to implant two lenses in each eye. The patient is satisfied with his postoperative vision and overall outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
9

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(56 citation statements)
references
References 1 publication
0
47
0
9
Order By: Relevance
“…[69][70][71][72] Together with surgeons performing piggyback implantation, our laboratory has been devoting constant efforts to determine the pathogenesis and management of this complication (Figures 7-9). [72][73][74][75] We have recently proposed clinical and pathological lessons for prevention and management of this entity (Pandey SK, Snyder ME, Werner L, Apple …”
Section: Introductionmentioning
confidence: 99%
“…[69][70][71][72] Together with surgeons performing piggyback implantation, our laboratory has been devoting constant efforts to determine the pathogenesis and management of this complication (Figures 7-9). [72][73][74][75] We have recently proposed clinical and pathological lessons for prevention and management of this entity (Pandey SK, Snyder ME, Werner L, Apple …”
Section: Introductionmentioning
confidence: 99%
“…В 1993 г. Gayton и Sanders предложили технологию имплантации «piggyback» ИОЛ для обеспечения «плюсовой» рефрак-ции при микрофтальмии [1]. Другие авторы последо-вательно использовали данный подход для коррекции гиперметропии высокой степени [2,3,4,5,6,7].…”
Section: имплантация «Piggyback» иол или замена иол?unclassified
“…The best markers of the quality of a biometry service are the percentage of eyes achieving a postoperative spherical equivalent refraction within 0.5 and 1.0D of the target refraction and the total range of refractive error (32). The Royal College of Ophthalmologists (RCOphth) 2004 cataract surgery guidelines state that both optical (partial coherence interferometry (PCI)) and acoustic (ultrasound) methods of axial length measurement can be routinely used (33), although it has been shown that PCI reduces the prediction error of postoperative refractive outcome.…”
Section: Refractive Surprises After Cataract Surgerymentioning
confidence: 99%